Camptodactyly Caused by an Anomalous Origin of the Flexor Digitorum Superficialis Tendon: A Case Report and Review of the Literature - Duci, Shkelzen B. (The Surgery Journal, 2019)
Camptodactyly is a flexion contracture of the proximal interphalangeal joints and is known as an isolated malformation that affects 1 in 300 in the population and can be inherited as an autosomal dominant trait with variable expression.A 17-year-old female was referred to the Clinic of Plastic Surgery, University Clinical Center of Kosovo, Prishtina, for the first time with camptodactyly of the little finger in the right hand. She was presented with a progressive flexion contracture of the proximal interphalangeal joint greater than 110 degrees of her right little finger.According to our observations from outpatient consultations, we concluded that the case of camptodactyly in the little finger in the flexible form (>110 degrees), which underwent surgical treatment, presented excellent result. Therefore, we think that the surgical technique used in our case report will contribute to treating this complicated deformity.
Keywords: contracture; flexion; result; treatment